2016
DOI: 10.7566/jpsj.85.083702
|View full text |Cite
|
Sign up to set email alerts
|

Optical Evidence of Itinerant-Localized Crossover of 4fElectrons in Cerium Compounds

Abstract: Cerium (Ce)-based heavy-fermion materials have a characteristic double-peak structure (mid-IR peak) in the optical conductivity [σ(ω)] spectra originating from the strong conduction (c)-f electron hybridization.To clarify the behavior of the mid-IR peak at a low c-f hybridization strength, we compared the σ(ω) spectra of the isostructural antiferromagnetic and heavy-fermion Ce compounds with the calculated unoccupied density of states and the spectra obtained from the impurity Anderson model. With decreasing c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The details of exchange-parametrization may therefore be different from the two doublet model investigated here. Further experimental evidence for multipeak hybridization gap structure in σ (ω) has also been found in Ce compounds [47].…”
Section: Discussionmentioning
confidence: 60%
“…The details of exchange-parametrization may therefore be different from the two doublet model investigated here. Further experimental evidence for multipeak hybridization gap structure in σ (ω) has also been found in Ce compounds [47].…”
Section: Discussionmentioning
confidence: 60%
“…An important effect of the SOI is a splitting of the Ce 4f bands from almost flat bands at ∼ 0.3 eV into two parts, namely 4f 5/2 bands at ∼ 0.2 eV and 4f 7/2 bands at ∼ 0.5 eV. The splitting energy is roughly 0.25 − 0.3 eV, which is a characteristic value for various Ce-based compounds as observed in σ 1 (ω) spectra [31,33] and photoelectron spectra [8,34].…”
Section: B Electronic Structure Of Cerh2as2mentioning
confidence: 88%
“…Figure 8 shows the temperature dependencies of the center of gravity [∆ ω = [ ω(T ) − ω(300 K) ] / ω(300 K) ], where ω(T ) = ω2 ω1 ωσ 1 (ω)dω/ ω2 ω1 σ 1 (ω)dω, and the spectral weight transfer [∆SW = ω2 ω1 [|σ 1 (ω, T ) − σ 1 (ω, 300 K)|/σ 1 (ω, 300 K)]dω] of the mid-IR peak of CeRh 2 As 2 relative to those at T = 300 K. The integration range was set as ω 1 = 0 eV ≤ ω ≤ ω 2 = 0.8 eV, where the spectral change in the lower energy region is almost recovered. In the figure, the evaluated ∆ ω and ∆SW of two heavy-fermion compounds CeCu 2 Si 2 (T K ∼ 10 K) [36] and CeNi 2 Ge 2 (T K ∼ several K) [33] are also plotted for comparison. The temperature dependencies of ∆ ω and ∆SW correspond to the evolution of the c-f hybridization with temperature [31], i.e., an increasing itinerancy corresponds to increasing values of ∆ ω and ∆SW whereas constant values suggest a localization of the 4f state.…”
Section: C-f Hybridization Of Cerh2as2mentioning
confidence: 99%
“…To obtain σ(ω) via KKA of R(ω) , the spectra were extrapolated using the Hagen-Rubens function below the lowest energy measured, and the free-electron approximation R(ω) ∝ ω −4 above the highest energy [37]. σ(ω) spectra of CeM 2 Ge 2 at 8-10 K have already been reported [23]. In this paper, we will report the temperature-dependent σ(ω) spectra of CeM 2 Ge 2 and Yb(Co x Rh 1−x ) 2 Si 2 (x = 0, 0.27) compared with those of CeCu 2 Si 2 [38], YbRh 2 Si 2 [39], and YbIr 2 Si 2 [40] to check the relation of the Kondo temperature to the temperature-dependent spectral change.…”
Section: Methodsmentioning
confidence: 99%
“…As for the mid-IR peak, Okamura et al found that the peak energy is proportional to the effective mass of the heavy quasiparticle, which is another feature of heavy-fermion systems [22]. On the other hand, Kimura et al showed that the behavior of the mid-IR peak changes could be explained by DFT calculations in the itinerant phase, but, across a quantum critical point (QCP), the behavior changes to that is explained by using the local character with an on-site Coulomb repulsion in the 4f states [23]. In other words, by investigating the appearance of the mid-IR peak, we can study the localized and itinerant characters of 4f states, as well as the typical electronic states of HF systems.…”
Section: Introductionmentioning
confidence: 99%